Examining youth perceptions and social contexts of litter to improve marine debris environmental education. Issue 9 (2nd September 2019) - Torres, Hannah R.; Reynolds, C. J.; Lewis, Anna; Muller-Karger, Frank; Alsharif, Kamal; Mastenbrook, Katie
Abstract: Youth have astute observations about site-specific personal and environmental factors that contribute to littering and marine debris, and they have a strong potential to act as change agents in communities. Interactions with youth in Pinellas County Florida add insights into a growing body of research on environmental education and marine debris prevention. This study assessed perceptions of marine debris and littering behaviors through group discussions with middle school and high school students ( N = ∼44), evaluations at summer camp programs ( N = ∼31) and pre- and post-assessments of environmental field trips (pre-assessment N = ∼120; post-assessment N = ∼140). Youth showed high initial awareness of the effects of marine debris on the environment but showed less understanding about the role of watersheds and biodegradation in marine litter issues. A majority of youth attributed others' littering behavior to dispositional factors, like laziness, while attributing their own littering to situational factors, like poorly placed bins. Student observations of educators and parents also influenced littering behaviors and willingness to act. To reduce littering, education and outreach programs need to (1) provide opportunities for ongoing assessment of complex marine debris topics, (2) align visual and written or verbal messages, (3) reduce actor/observer bias related to littering behaviors, and (4) support adult role models.